SWAMEDIKASI PADA PENDERITA COVID-19 MENJALANKAN ISOLASI MANDIRI DI WILAYAH JAKARTA PADA TAHUN 2021 - Wardiyah Wardiyah; Adin Hakim Kurniawan; Dinda Unique Valentine (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
COVID-19 or Coronavirus disease 2019 is a pandemic in the end of 2019. Currently, several studies for the therapy of COVID-19 have been carried out, but specific drugs that have been proven effective and safe to treat it do not available yet. Self medication is expected to reduce the severity of sufferers and also spreading of COVID-19 in Indonesia. Patient without symptoms or mild symptons can self isolated and do self medication. Patients with self medication can use drugs to treat symptoms, immune boosting drugs, such as multivitamin or herbal medicines. The purpose of this study is to find out the illustration of Jakarta's self medication pattern for COVID-19 patients who are self-isolating in 2021. This study aims to describe the pattern of self-medication in self-isolated COVID-19 patients in the Jakarta area in 2021. This research uses quantitative descriptive. The technique uses purposive sampling and gets 100 respondens. The data collection is collected by making questioners and analysed by univariat. From the results of data processing, it is known that the tests carried out by PCR Swab were 49 people (69%). The symptoms felt were fever as much as 22.3%. The drug consumed is paracetamol by 45.1%. The supplements consumed were vitamin C by 38.7%. Sources of information are friends/family by 61.4%. The place to get medicines/supplements/traditional medicines is pharmacies by 40% (38 people).